Determination of dynamic and traction-energy indicators of all-wheel-drive traction-transport machine - Antoshchenkov, Roman; Bogdanovich, Serhii; Halych, Ivan; Cherevatenko, Halyna (Eastern-European Journal of Enterprise Technologies, 2023)
The results of a study of dynamic and traction-energy indicators of an all-wheel drive wheeled traction-transport machine are presented. A diagram of a dynamic transmission model for an all-wheel drive wheeled traction and transport machine and a system of equations for the transmission dynamics in the Cauchy form have been compiled. This made it possible to determine the dependences of the angular speeds of rotation of the transmission elements of the traction-transport machine, the dependences of the torques and the dependences of the contacting traction forces on the wheels on time. The method allows to determine the optimal transmission parameters, differential designs and gear ratios to improve the traction and coupling and fuel-economic performance of the machine. It has been established that the angular speeds of rotation of the front wheels of the traction-transport machine 1.29 rad/s, 1.27 rad/s are higher than the angular speeds of rotation of the rear wheels 1.24 rad/s, 1.25 rad/s, which leads to the appearance of a kinematic discrepancies and additional energy losses. The torques of the front drive wheels are 6972 Nm, the rear drive wheels are 4622 Nm. The contacting traction forces on the front wheels of the machine are 5478 N after the end of the acceleration of the machine, on the rear wheels – 3473 N. Experimental studies were carried out on the example of an all-wheel drive wheeled tractor with an articulated frame to validate the method for assessing the dynamics of the traction-transport transmission. The difference between the values of the angular speeds of rotation of the wheels and the tangential traction forces on the wheels, determined theoretically and obtained during experimental studies, is 2 %. The developed method for assessing the transmission dynamics of an all-wheel drive traction and transport machine should be considered valid. The method proposed in the paper can be used to assess the dynamics of wheeled machines